Pengaruh subsidi pertanian terhadap kesejahteraan petani padi di Desa Bagan Serdang, Kecamatan Pantai Labu, Kabupaten Deli Serdang - Silvi Annur Hasibuan; Monika Flora Manik; Rini Khairani Harahap; Amelia Amelia; Evi Suriyani Harahap (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to explore the impact of agricultural subsidies, including fertilizer subsidies, seed subsidies, and credit subsidies, on the welfare of rice farmers in Bagan Serdang Village, Pantai Labu District, Deli Serdang Regency. A quantitative method was applied using multiple linear regression analysis using SPSS 25 software. The sample used in this study consisted of 50 rice farmers who were selected as respondents through questionnaire distribution. The findings of this study revealed that subsidies for fertilizer and seeds have a positive and significant impact on farmers' welfare, while credit subsidies have a negative but significant impact. This is caused by pressure to repay credit, misallocation of funds, or the ineffectiveness of credit facilities used by farmers. Overall, the three types of subsidies have a significant impact on farmers' welfare with an R2 value of 0.533, indicating that 53.3% of the variation in farmers' welfare can be explained by these three subsidies. These results emphasize the importance of effective distribution of fertilizer and seed subsidies to improve farmers' welfare, while the management of credit subsidies must be reviewed to avoid placing a financial burden on farmers.